"EPIDEMIOLOGY OF BRUCELLOSIS IN ISFAHAN (SEASONAL VARIATION IN MILK CONTAMINATION WITH BRUCELLA)" - A. Owrang; A. Nadim (Tehran University of Medical Sciences, 1972)
Milk samples were collected once every two weeks from 69 milk distribution centers for a period of one year. The samples were examined for Brucella infection by means of a ring test. It was shown that the infection of milk has no relation to any special season. Cattle, sheep and goat milk were all found infected. Some of the positive milk specimens were cultured and Brucella was isolated.